Comparative Evaluation of Compressive Strength in Earth Blocks Enhanced with Natural Fibers - Narayan, Sumesh; Maharaj, Ravikesh Rahul; Kumar, Romitesh; Kishore, Thomas; Salahuddin, Md; Mamun, Kabir (Civil Engineering Journal, 2024)
Portland cement is a key component in the production of concrete blocks; however, its production has an extensive carbon footprint that contributes towards climate change. In addition, the availability of aggregates is also often challenging and, as such, leads to production delays of concrete blocks, which ultimately causes delays in the completion of construction projects and constant price increases. The price increase of construction materials such as concrete blocks tends to affect the quality of houses being constructed in rural communities of the Pacific Island Countries (PICs), and this calls for the development of a low-cost alternative to ensure housing quality is not compromised. This project is being carried out to develop earth blocks as an environmentally friendly and sustainable substitute for concrete blocks that are widely used in the construction industry. Coir (derived from coconut fibers) and bamboo fibers were incorporated into these blocks as reinforcement materials, aiming to achieve the same level of strength required for use in construction. Additional adhesion of the earth block was provided by the usage of cement. The earth blocks were cured for 7, 14, and 28 days, after which they were subjected to various tests, including a compressive strength test, water absorption test followed by wet compressive strength test to compare its performance to ensure it has sufficient strength for it to be introduced into the market as a more eco-friendly, low-carbon-emission, and cost-effective construction material. The maximum compressive strength obtained during the test was 3.24 MPa. Following a comprehensive analysis of the data attained, the composition of 15% cement and 0.75% bamboo fiber emerges as the most ideal choice for creating marketable earth blocks. This composition strikes a balance between providing adequate strength and ensuring minimal reduction in overall strength when the blocks are exposed to wet conditions. Doi: 10.28991/CEJ-2024-010-10-013 Full Text: PDF